Reactive flame retardant with core‐shell structure and its flame retardancy in rigid polyurethane foam. Issue 46 (24th August 2015) - Luo, Fubin; Wu, Kun; Li, Yinwen; Zheng, Jian; Guo, Huilong; Lu, Mangeng
ABSTRACT With a shell of poly (methyl methacrylate‐co‐hydroxyl ethyl acrylate) (PMMA‐HA), microencapsulated ammonium polyphosphate (MHAPP) is prepared by in situ polymerization. The core‐shell structure of the reactive flame retardant (FR) is characterized by Fourier transform infrared (FTIR) and scanning electron microscopy/energy dispersive spectroscopy (SEM/EDS). The results of water leaching rate and water contact angle measurements show that ammonium polyphosphate (APP) is well coated by a hydrophobic shell. Due to the presence of active groups (–OH) and hydrophobic groups (–CH3) in shell, MHAPP exhibits better compatibility, flame retardancy, and water resistance compared with neat ammonium polyphosphate (APP) in rigid polyurethane foam (PU). Compression strength of PU/MHAPP with suitable loading is higher than that of PU/APP and PU, the reason is that the active groups in shell can improve the compatibility of MHAPP in PU composite. From thermal stability and residue analysis, it can be seen that the presence of reactive flame retardant shows positive effect on thermal stability of PU composite at high temperature, results also indicate that MHAPP can promote the carbonization formation efficiency of PU composite during combustion process compared with APP. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42800.